Urgensi Pendaftaran Perjanjian Bersama Hasil Perundingan Bipartit Dalam Sistem Penyelesaian Perselisihan Hubungan Industrial Di Indonesia - Akmalia, Iftita; Rizqi, Aditya Maulana (JATIJAJAR LAW REVIEW, 2025)
Disputes between employers and employees are a common occurrence in industrial relations. Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes stipulates that bipartite settlement must be attempted before resorting to litigation. The results of bipartite agreements are outlined in a Collective Agreement, which is binding and must be registered with the Industrial Relations Court. This article aims to examine the urgency of registering Collective Agreements to strengthen legal certainty and protect both parties. This research uses a normative juridical method with a statutory and conceptual approach. The study shows that registering a Collective Agreement has important legal consequences in streamlining the implementation of the agreement and serving as a basis for enforcement in the event of default. Therefore, fulfilling this registration obligation is a strategic step in creating legal certainty in industrial relations.